Factors influencing fast food consumption: a case study of suburban residents, Malaysia / Nur Ain Nabila Azmi ... [et al.] - Azmi, Nur Ain Nabila; Abd Majid, Hairul Nizwan; Mohd Zahari, Mohd Salehuddin; Bashir, Muhammad 'Arif Aizat; Kamis, Rohaiza (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
The fast-food sector has expanded all over the world, not only in cities but also in suburbs. Many fast food restaurants are likely to open new locations, especially those in suburban areas. Individual habits appear to influence the elements that contribute to fast food intake. This study intends to discover whether the suburban environment influences an individual's consumption intention, as well as to identify the components that contribute to fast food consumption and to assess the function of advertising. Suburban areas have a lot of potential to contribute to the rapid expansion of the fast-food business. Unfortunately, there has been a shortage of research that investigates the elements that influence suburban inhabitants to consume fast food; the theory of planned behavior (TPB) was employed as a foundation for this study. The data obtained were analysed using SPSS v26 which involves frequency analysis, descriptive analysis, reliability analysis, Pearson correlation, and moderating analysis. The analysis performed on 126 respondents’ data collected in Kemaman, Terengganu through questionnaires tests the conceptual hypotheses. The study's findings may be of some assistance to the industry and have added significant data that other studies can use. Furthermore, by including a new role in TPB, advertisement, this work may provide a new body of knowledge.